2022
DOI: 10.1038/s41598-022-17776-x
|View full text |Cite|
|
Sign up to set email alerts
|

Efficient genome editing in wild strains of mice using the i-GONAD method

Abstract: Wild mouse strains have been used for many research studies, because of the high level of inter-strain genetic and phenotypic variations in them, in addition to the characteristic phenotype maintained from wild mice. However, since application of the current genetic engineering method on wild strains is not easy, there are limited studies that have attempted to apply gene modification techniques in wild strains. Recently, i-GONAD, a new method for genome editing that does not involve any ex vivo manipulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Since i-GONAD was first described in 2015 [6], the procedure has been adopted by several research laboratories. i-GONAD has been optimized for inbred strains such as B6 [19], and it has been used to generate GM wild mice [29]. However, we showed here that the RNP treatment or the electroporation negatively impacted embryo survival even when using the optimal constant 100 mA current for electroporation.…”
Section: Discussionmentioning
confidence: 64%
“…Since i-GONAD was first described in 2015 [6], the procedure has been adopted by several research laboratories. i-GONAD has been optimized for inbred strains such as B6 [19], and it has been used to generate GM wild mice [29]. However, we showed here that the RNP treatment or the electroporation negatively impacted embryo survival even when using the optimal constant 100 mA current for electroporation.…”
Section: Discussionmentioning
confidence: 64%
“…Researchers at NIG applied CRISPR-based genome editing using the i-GONAD method. Using this method, they showed that it is possible to efficiently modify genes in most wild strains (seven out of the nine strains examined) [48]. These findings suggest that i-GONAD will contribute to the development of many wild GM strains in the future, which will also be helpful for future studies.…”
Section: I-gonad-based Production Of Wild Mouse Strainsmentioning
confidence: 90%
“…Advancements in CRISPR/Cas9 technology have expanded the horizons of genetically modified organisms, moving beyond the confines of traditional model species to now include non‐model animals and strains (Dickinson et al., 2020; Imai et al., 2022; Mendoza & Trinh, 2018). Such breakthroughs allow researchers to scrutinize gene functions in animal species and strains that are more aligned with their research objectives.…”
Section: Discussionmentioning
confidence: 99%